Strategi Peningkatan Kemandirian Energi melalui Pemanfaatan Panel Surya untuk Hidroponik dan Akuaponik di SDI As Salam dan SMPIT As Salam Kota Malang - Putu Hadi Setyarini; Sisca Fajriani; Tri Nurwati; Mochammad Roviq; Dian Inayati (Jurnal Surya Masyarakat, 2024)
The community service activity at SDI As Salam and SMPIT As Salam aimed to enhance energy independence through the integration of solar panels in hydroponic and aquaponic systems. Solar panels were utilized as an alternative energy source to reduce dependency on PLN electricity, which posed major challenges for water pump operations in hydroponic and aquaponic farming systems. The Participatory Rural Appraisal approach was implemented through technical training, solar panel installation workshops, and farming assistance. The results demonstrated that using solar panels reduced electricity costs, supported students' learning about renewable energy, and improved the sustainability of urban farming in schools. The integration of solar panels with hydroponic and aquaponic systems provided a practical and eco-friendly solution to energy challenges for farming on limited land.